Terapi Menulis Ekspresif untuk Meningkatkan Regulasi Emosi pada Remaja di SMP X Yogyakarta - Sani Putri; Zahro Varisna Rohmadani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine the effectiveness of expressive writing therapy treatment to improve emotional regulation in adolescents. This research method uses pre-experimental with the form of One Group Pretest-Postest design. The subjects of this study were 8 adolescents at SMP X Yogyakarta using purposive sampling techniques. Expressive writing therapy intervention with an implementation time of 40 minutes was carried out 4 days in two weeks. The data analysis method used was nonparametric statistics of the Wiloxon Signed Rank Test technique to test the difference in the emotional regulation score of the subject group during the prestest and possttest. The results of the Wiloxon Signed Rank Test showed that expressive writing therapy was effective in improving emotion regulation with p=0.012